2005
DOI: 10.1289/ehp.7077
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Look at Fluorosis, Fluoride Exposure, and Intake in Children Using a Health Risk Assessment Approach

Abstract: The prevalence of dental fluorosis in the United States has increased during the last 30 years. In this study, we used a mathematical model commonly employed by the U.S. Environmental Protection Agency to estimate average daily intake of fluoride via all applicable exposure pathways contributing to fluorosis risk for infants and children living in hypothetical fluoridated and non-fluoridated communities. We also estimated hazard quotients for each exposure pathway and hazard indices for exposure conditions rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(82 citation statements)
references
References 25 publications
3
71
1
4
Order By: Relevance
“…Similar observations were reported in the US, Canada, Chile, and other countries (Ismail and Messer, 1996;Karthikeyan et al, 1996;Villa et al, 1998;Kumar and Swango, 1999). Erdal and Buchanan (2005) stated that some children in the US may be at risk of dental fluorosis considering multi-pathway fluoride intakes. Morgen et al (1998) reported that 69% of children 7-11 years of age examined in a suburban Boston pediatric practice were found to have dental fluorosis.…”
Section: Introductionsupporting
confidence: 73%
“…Similar observations were reported in the US, Canada, Chile, and other countries (Ismail and Messer, 1996;Karthikeyan et al, 1996;Villa et al, 1998;Kumar and Swango, 1999). Erdal and Buchanan (2005) stated that some children in the US may be at risk of dental fluorosis considering multi-pathway fluoride intakes. Morgen et al (1998) reported that 69% of children 7-11 years of age examined in a suburban Boston pediatric practice were found to have dental fluorosis.…”
Section: Introductionsupporting
confidence: 73%
“…Fluorosis affects developing, unerupted and erupted permanent teeth of children who are below the age of six years [11], which again affects appearance of teeth and causes emotional disturbance. American Association of Poison Control Centers reported 21, 513 calls which were related to fluoride tooth patse ingestion [12].…”
Section: Introductionmentioning
confidence: 99%
“…This study cannot comment on overall exposure to fluoride, although drinking water is usually the largest contributor to fluoride intake [2,12].…”
Section: Discussionmentioning
confidence: 99%